An analysis of student portal’s experiences at the Zimbabwe Open University Manicaland Regional Campus - Mzizi, Lynn; Mwareya, Nicholas; Mukaro, Juliet; Mapfunde, Davie; Chipika, Charles Govero (ARKA INSTITUTE, 2025)
In line with the international fraternity, the Zimbabwe Open University has adopted open and distance e-learning (ODeL) technology that uniquely empowers its teaching and learning approach. After creating the first version of My Vista that was fully functional in 2017, the Information Technology department in its efforts to continuously improve and empower students, created a new version of the My Vista student portal in 2022, which was made available to students and lecturers in January 2023. The old My Vista had its own challenges, hence the new version was created. This study is informed by the following objectives, to establish the accessibility of the new student portal to the students in conducting e-learning at the Zimbabwe Open University Manicaland Campus. To identify the e-learning challenges faced by students whilst using the My Vista student portal. To ascertain the e-learning reasons for students’ dropouts at the Zimbabwe Open University. This study is based on the critical realism paradigm that considers reality based on social, political and economic contexts, a recent qualitative study complemented by digital ethnography as a research strategy to collect data from online platforms, attempts to analyze the e-learning portal experiences of students at ZOU Manicaland regional campus. The results showed that students face challenges in accessing the new student portal due to technical issues, lack of timely induction by the university, and issues related to the digital divide. It is recommended that the institution is asked to continuously update its system and increase the Wifi band coverage.